Cyberbullying Experiences and Coping Strategies in Ibadan Metropolis, Ibadan, Nigeria - Kehinde, Ayodeji M.; Dipeolu, Isaac O. (European Scientific Journal, ESJ, 2023)
Introduction/Aim: Cyberbullying of influential personalities or celebrities is a media menace. Psychological, depressional, and emotional suicidal ideation effects are some of the impacts on celebrities. A few studies have investigated celebrities’ coping mechanisms against this, with the majority from developed countries. There is a dearth of information on this among celebrities in Nigeria. This study investigated the experience, effects, and coping mechanisms of cyberbullying among celebrities in the Ibadan metropolis, Oyo State, Nigeria. Material and method: A descriptive crosssectional purposive sampling method was adopted. An in-depth interview guide was used for data collection among 14 consented celebrities. Data were manually analysed thematically. Results: Most participants were 25-35 years old and were comedians. All have experienced cyberbullies, such as popularity attacks and defamation of character. The effects of cyberbullying on the victims include low self-esteem, mental stress, depression, substance abuse, and financial crisis. Jealousy, hatred, envy, and quest for popularity among the perpetrators fuelled this menace. However, some celebrities have overcome these effects through technical, preventive, corrective, social support, and spiritual approaches. Conclusion: Cyberbullying is prevalent among celebrities and many experienced psychological effects. Awareness, interventions aimed at its prevention, and adequate coping strategies are needed to solve this menace.